Effects of Parenting Styles and Family Contributors on Physical Activity Behaviors in Arab Children Ages 6-10 Years Old Living in the US - Tami, Suzan; Reed, Debra (International Journal of Child Health and Nutrition, 2020)
The purpose of this study was to explore the effects of parenting styles and family contributors on physical activity behaviors in Arab children living in the US. This mixed-method study included the Caregiver's Feeding Style Questionnaire (CFSQ), Family Nutrition Physical Activity (FNPA) survey, and five focus group discussions (FGD), guided by the Social Cognitive Theory (SCT). Twenty-three Arab mothers of 37 children aged 6-10 years old participated in this study. Seventeen mothers were overweight or obese, and six children were overweight or obese. Although all Arab mothers self-assessed that they were authoritative, only seven mothers were categorized as having an authoritative feeding style based on their CFSQ scores. The FNPA overall mean was 3.15, indicating less obesogenic family environments and behaviors. Across FGDs, common physical activity barriers included lack of time, the child being distracted by technology, and lack of a mother's interest in a child's physical activity due to culture and fear. Positive approaches included considering the child's interest in sports and involvement in physical activity with the child. Negative attitudes included pushing the child to do sports and the mother's lack of interest in physical activity. In correlation analyses, the mother's BMI was significantly correlated with the child's BMI z-scores (r = 0.325, p = 0.005). No significant associations were found between reported feeding styles (CFSQ), obesogenic family environments (FNPA), and child's BMI z-scores. This study can guide future efforts in developing effective education programs, including physical activity behaviors for Arab families.